2019
DOI: 10.1002/met.1850
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of landfalling Bay of Bengal cyclones during 2013 using the high resolution Weather Research and Forecasting model

Abstract: The present study investigated the capability of the Weather Research and Forecasting (WRF) model in the forecast/simulation of five landfalling Bay of Bengal (BoB) cyclones during 2013. A 3D variational (3DVar) method of data assimilation of the WRF model was used to assimilate the Global Telecommunication System and satellite radiances to improve the initial conditions. The results demonstrated that the model has the ability to simulate the cyclone track, intensity and structure. The study also indicates tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Amphan is considered at 00 UTC on 19 May 2020, Fani at 03 UTC on 02 May 2019, Hudhud at 12 UTC on 11 October 2014, Phailin at 12 UTC on 11 October 2013, and Sidr at 03 UTC on 15 November 2007. The positive (negative) anomaly indicates the temperature is warmer (cooler) than the normal temperature, and for the model, it is calculated using temperature at a given time minus the average temperature during the entire simulation period [58]. From satellite observation, it is noticed that in most cyclone cases, the maximum warm core varies from 9 km to 15 km in height.…”
Section: Evaluation Of Model Predictions Using Statistical Methodsmentioning
confidence: 99%
“…Amphan is considered at 00 UTC on 19 May 2020, Fani at 03 UTC on 02 May 2019, Hudhud at 12 UTC on 11 October 2014, Phailin at 12 UTC on 11 October 2013, and Sidr at 03 UTC on 15 November 2007. The positive (negative) anomaly indicates the temperature is warmer (cooler) than the normal temperature, and for the model, it is calculated using temperature at a given time minus the average temperature during the entire simulation period [58]. From satellite observation, it is noticed that in most cyclone cases, the maximum warm core varies from 9 km to 15 km in height.…”
Section: Evaluation Of Model Predictions Using Statistical Methodsmentioning
confidence: 99%
“…However, few studies focused on improving the vortex initialization by using better satellite and reanalysis data (Nadimpalli, 2020a;Nadimpalli, 2020b). In addition to SST, atmospheric high temperature and diabatic heating also plays a dominant role in the evolution of the intensity and determining the track of TC (Singh and Bhaskaran, 2020). Henceforth, many studies confirmed the direct correlation between seasonal changes and TC formation.…”
Section: Role Of Atmospherementioning
confidence: 99%
“…They conclude that the downscaled model significantly improves the spatial distribution of rainfall, maximum vorticity evolution, wind, and temperature profiles for mature phase cyclones. Studies specifically examining the BoB simulations [8][9][10] typically make empirical comparisons of TC simulations at ~10 km resolution against observationally based data, but often with an India-centric domain that contains a larger number of landfalling events. By contrast, in this study we specifically focus on Bangladesh, with simulations at higher resolution.…”
Section: Background and Summarymentioning
confidence: 99%